A Bioactive Fraction From The Leaves Of Ceiba Pentandra (L.) Gaertn. Exhibits Antiproliferative Activity Via Cell Cycle Arrest At The G1/S Checkpoint And Initiation Of Apoptosis Via Poly [ADP-Ribose] Polymerase 1 (PARP1) Cleavage In Hela Cells. - Addy, B.S.; Nyarko, E.N.Y.; Firempong, C.K. (Journal of Ethnopharmacology, 2025)
Ethnopharmacological relevance: Ceiba pentandra (L.) Gaertn. (Malvaceae) has been used in Africa traditionally to manage a variety of illnesses, including cancer. The hydroethanolic extract of the leaves of C. pentandra has been shown to possess antiproliferative activity. However, the fractionation of antiproliferative bioactive constituents from the leaves of C. pentandra and the determination of the mechanisms of action of such bioactive constituents remain unexplored. Aim of the study: This work sought to fractionate the extract of C. pentandra leaves, establish the antiproliferative activity of the fractionated constituents, and determine the active constituents’ possible mechanisms of action. Material and methods: Chromatographic techniques were used to fractionate bioactive constituents from C. pentandra leaves. The fractionated constituents were evaluated for their antiproliferative activity against four cancer cell lines (viz hepatocellular carcinoma, colorectal adenocarcinoma, cervical carcinoma, and mammary adenocarcinoma) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT)-based assay. The possible mechanisms of action of the active constituent, Fraction A (IsoA), were also determined via western blot analysis. Results: Six constituents were fractionated from the leaves of C. pentandra. Among the six constituents, IsoA stood out for its remarkable antiproliferative activity across the four cancer cell lines, with hepatocellular carcinoma (HepG2) cells being the most affected. With half-maximal inhibitory concentration (IC50) values ranging from 6.4 ±1.2 μg/mL to 19.2±3.4 μg/mL, IsoA demonstrated great potential in inhibiting cancer cell proliferation. Notably, IsoA’s mechanisms of action involve critical molecular targets associated with cell cycle regulation and apoptosis. It significantly increased the levels of phosphorylated cyclin-dependent kinase 2 (Cdk2 pTyr15), a key regulator of cell cycle arrest, and cleaved poly [ADP-ribose] polymerase 1 (PARP1), a hallmark of apoptosis initiation. These findings underscore the therapeutic potential of IsoA in cancer treatment. Conclusions: IsoA demonstrated highly promising in vitro antiproliferative activity by effectively arresting the cell cycle at the G1/S checkpoint, halting cancer cell proliferation. Additionally, IsoA induced programmed cell death (apoptosis) through mechanisms such as PARP1 cleavage, highlighting its potential as a candidate for cancer therapy.
Research Article
Keywords: Antiproliferative Activity; Cell Cycle Arrest; Mechanism of Action; PARP1 Cleavage; Cdk2; G1/S checkpoint; Apoptosis; Ceiba Pentandra